Size and dynamics of order-of-entry effects in pharmaceutical markets. (January 2018) - Porath, Daniel
In anticipation of long-run competitive advantages, pharmaceutical companies often try to enter new markets earlier than their competitors. It is questionable, however, whether this effort is really justified, because knowledge about the expected size of these order-of-entry advantages is scarce. Apart from confirming the existence of long-run advantages for the first mover for some selected brands, the literature gives hardly any guidelines. The objective of this article is to provide the information on the existence, the size, and the dynamics of order-of-entry effects, which is necessary for deciding on the optimal moment for a launch. The author proposes a new framework—a fractional panel probit model—which is fitted to a big and representative sample. With this procedure, order-of-entry effects can be measured in a multivariate model and as absolute market share differences, which is more informative for pharmaceutical companies than former measures.